A Critical Discourse Analysis of Ideological Representations of Indonesia’s August 2025 Protests in Arabic Media - Najmi Syofyan; Ulil Abshar (UIN Salatiga, 2026)
This study examines how three Arabic-language news organizations, namely Al Jazeera Arabic, Asharq Al-Awsat, and Okaz, report protests in Indonesia. The study uses Norman Fairclough's Critical Discourse Analysis (CDA) method to analyze news through the lens of social practices that reinforce ideology and power relations, rather than as an objective portrayal of reality. News collected from the official websites of each media outlet and analyzed at the textual, discourse, and social levels forms the research data. Qualitative linguistic analysis is used as the methodology in this study. The findings indicate that these media outlets have very different ideologies. By presenting the social grievances of the protesters and being careful not to criticize the state, Al Jazeera Arabic succeeds in providing a fairly diverse narrative. While Asharq Al-Awsat relies on official sources to highlight the themes of order and security, Okaz uses symbolic delegitimization to portray the protests as a threat to national stability. Studies like this reinforce the idea that the ideological leanings and political agendas of different Arab media influence how the public perceives political protests in Indonesia.